PERNIKAHAN PADA WAKTU IHRAM MENURUT IMAM SYAFI’I DAN IMAM ABU HANIFAH - Mubarok, M. Husni; Arif, Suyud (IBN KHALDUN BOGOR, 2013)
Marriage is not just a meeting between two beings process alone. However, marriage is a big gate which is the mouth of the meeting between the two families, two tribes, cultures, and it could be two states. Getting married is human nature to channel instincts of love of the opposite sex, and therefore Islam makes marriage a legitimate way for humans to maintain the existence of the regeneration and survival of offspring. However, there are concerns about the law of marriage at the time of Ihram, particularly in view of Imam Shafi'i and the imam of Abu Hanifa.